Implementation of Teacher Professional Education Program for English Language Teachers at Universitas Muhammadiyah Sidenreng Rappang - Usman M; Sam Hermansyah; M Nurzin R Kasau; Hasan Hasan (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the implementation of the Teacher Professional Education Program (Pendidikan Profesi Guru or PPG) for English Language Teachers at Universitas Muhammadiyah Sidenreng Rappang (UMSR). The research aims to explore the effectiveness of the program in enhancing the professional competencies of teachers, particularly focusing on pedagogical skills and content knowledge. A qualitative approach was employed, utilizing document analysis, semi-structured interviews, and field observations to gather insights from faculty members, program coordinators, and teacher participants. The results of the study reveal that while the PPG program has significantly contributed to improving the teaching skills of participants, several challenges persist, including issues related to infrastructure, internet connectivity, and teacher preparedness, particularly in rural areas. Despite these challenges, the blended learning model combining online instruction and face-to-face workshops has proven effective in delivering flexible learning opportunities for teachers. Additionally, the Practice Teaching and Field Practice (PPL) components provided valuable hands-on experience, allowing participants to apply theoretical knowledge in real classroom settings. The findings suggest that continuous support from the government and educational institutions is crucial for addressing the remaining obstacles and ensuring the long-term success of the PPG program. This study contributes to the broader understanding of teacher professional development in Indonesia and highlights the need for ongoing investment in education to improve teaching quality